Phenotypic plasticity in Mercurialis annua : the role of signal detection and response in sex determination - Harris, Sue-Re (Department of Biological Sciences, 2017)
Mercurialis annua has been found to show phenotypic plasticity in terms of their sexual strategies. In androdioecious populations (males coexisting with cosexes), genetically labile males function as cosexes at low densities. At high densities, the frequency of males increases, while cosexes respond by increasing biomass allocation to the female function. Phenotypic plasticity in this species is likely a result of environmental detection. This study investigated possible mechanisms for density detection. Greenhouse experiments showed that Mannua responded to an above ground signal by increasing male frequency and male frequency was related to the proportion female allocation in cosexes. Individuals that were isolated from each other below ground and treated with leachate (collected from high density populations) responded by increasing allocation to female function while male frequency decreased. There is most likely an interaction between below and above ground sensing and response to the environment in M annua.